Microbial Distribution and Antibiotic Susceptibility of Lower Respiratory Tract Infections Patients From Pediatric Ward, Adult Respiratory Ward, and Respiratory Intensive Care Unit - Duan, Nan; Du, Jialin; Huang, Chenwei; Li, Haixia (Frontiers in Microbiology, 2020)
Introduction: Lower respiratory tract infections (LRTIs) account for significant morbidity and mortality in patients admitted to hospitals worldwide, especially in children and elderly. The prevalent microorganisms and antibiotic susceptibility were investigated among LRTI patients from the pediatric ward, adult respiratory ward and respiratory intensive care unit (RICU) in order to achieve more efficient treatment protocols and better recovery. Methods: In this retrospective cross-sectional study (January 2016 to December 2019), 4161 positive culture samples out of 18798 different specimens (9645 respiratory tract samples and 9153 blood samples) from LRTI patients were analyzed for pathogen incidence and antibiotic sensitivity. Results: Among the respiratory tract cultures, the frequency of Gram-negative bacterial strains was higher than Gram-positive bacterial strains. Pseudomonas aeruginosa was the dominant pathogen in both the adult respiratory ward (n=156, 21.49%) and RICU (n=975, 35.67%), whereas Staphylococcus aureus (n=66, 19.19%) was the most common bacterium in the pediatric ward. Among the blood cultures, Gram-positive bacteria remained the major microorganisms involved in LRTIs, and the most frequent pathogen was Staphylococcus epidermidis (n=59, 47.20%) in the pediatric ward and Staphylococcus aureus (n=10, 21.8%) in adult respiratory ward. However, Gram-negative bacteria were the main pathogens in the RICU, of which Klebsiella pneumoniae (n=51, 27.57%) is the most prevalent. Pseudomonas aeruginosa of LRTI patients remained highly susceptible (>70%) to routine antibiotics in pediatric ward. However, it only had high susceptibility to amikacin, tobramycin, gentamicin in both the adult respiratory ward and RICU and its antibiotic sensitivity to meropenem and imipenem was moderate in the adult respiratory ward and mild (<30%) in the RICU. Staphylococcus aureus isolated from LRTI patients was highly susceptible to linezolid, daptomycin, teicoplanin, vancomycin, tigecycline, rifampicin and trimethoprim/sulfamethoxazole in all three wards, moderately susceptible to gentamicin in both the adult respiratory ward and RICU and to clindamycin, oxacillin, moxifloxacin only in the adult respiratory ward. Conclusions: Microbial distribution and their patterns of antibiotic susceptibility revealed a high divergence among LRTI patients admitted to different wards in this hospital. Thus, different antibiotic therapies should be considered for distinct age groups.